2006
DOI: 10.1097/01.smj.0000197298.48311.80
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ilioinguinal-iliohypogastric Nerve Block Versus Spinal Anesthesia for Inguinal Herniorrhaphy

Abstract: The use of IHNB for patients undergoing herniorrhaphy resulted in a shorter time-to-home readiness, quicker oral intake post surgery, and no need for recovery room care, when compared with the use of SA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
1
12
1
3
Order By: Relevance
“…In a retrospective analysis, iliohypogastric-ilioinguinal nerve block for patients undergoing herniorrhaphy was associated with an earlier oral intake postsurgery and no need for recovery room care when compared with spinal anaesthesia. 174 Complications. Despite the fact that the target structures are in close relationship with sensitive anatomical structures (e.g.…”
Section: Ilioinguinal or Iliohypogastricmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective analysis, iliohypogastric-ilioinguinal nerve block for patients undergoing herniorrhaphy was associated with an earlier oral intake postsurgery and no need for recovery room care when compared with spinal anaesthesia. 174 Complications. Despite the fact that the target structures are in close relationship with sensitive anatomical structures (e.g.…”
Section: Ilioinguinal or Iliohypogastricmentioning
confidence: 99%
“…For patients after hernia repair, the use of ilioinguinal and iliohypogastric nerve blocks led to an earlier hospital discharge [median 18 h (range 14-26) vs 23 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26), P¼0.007, 169 mean 14.1 h (SD 1.5) vs 42.8 (5.3), P,0.001]. 174 These findings, combined with improved functional recovery, suggest that this block is a cost-effective intervention for patients undergoing hernia repair. 174 These findings were not reproduced in female patients undergoing surgery of the reproductive tract.…”
Section: Ilioinguinal or Iliohypogastricmentioning
confidence: 99%
“…Bleeding, hematoma, 18 and higher failure rates along with prolonged time to micturition 19 and return of motor strength may be a cause of delayed discharge. 20 There is also a potential for LA toxicity. Hashizume et al 16 compared the plasma concentrations of LAs after caudal block and found that it was more likely to be higher and possibly toxic when one LA was used than when a mixture was used.…”
Section: Discussionmentioning
confidence: 99%
“…[8] IH onarımı yapılan 126 erişkin blok uygulama ve yeterli duyusal blok gelişmesine kadar geçen toplam süre SA uygulanan hastalardan daha uzun olmaktadır.…”
Section: Discussionunclassified
“…[6,7] Bununla beraber inguinal herni cerrahisinde anestezi tekniği olarak IHNB'nin uygulandığı klinik çalışma az sayıdadır. [8] Çalışmamızın amacı, tek taraflı inguinal herni cerrahisi planlanan erişkin hastalarda IHNB uygulaması ve SA tekniklerinin; blok uygulama ve duyusal blok oluşma süreleri, ameliyatta hemodinamik etkiler, ameliyat sırasında sedasyon ihtiyacı, ameliyat sonrası dönemde duyusal bloğun sonlanma süreleri, ilk mobilizasyon süreleri, ameliyat sonrası analjezik tüketi-mi, taburculuk kriterlerine ulaşma zamanı, yan etkiler ile hasta ve cerrah memnuniyetini karşılaştırmaktır.…”
Section: Introductionunclassified